MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI PENGGUNAAN BALOK ANGKA PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK NEGERI PEMBINA DESA POLEWALI KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Nasaruddin R (Fakultas Keguruan dan Ilmu Penidikan UIM, 2019)
Abstract: Improving the Ability to Recognize the Number Symbols through the Use of Number Beams in Children Aged 5-6 Year at Taman Kanak-Kanak Negeri Pembina Polewali Village, Gantarang District, Bulukumba Regency. The purpose of this study was to determine the use of numeric blocks in improving the ability to recognize the number symbols of children aged 5-6 years in the Taman Kanak-Kanak Negeri Pembina Polewali Village, Gantarang District, Bulukumba Regency. The approach used in this research was a qualitative approach and the type of research was Classroom Action Research (CAR). The focus of this research was the ability to recognize symbols and numbers. Research procedures included planning, implementing actions, observing, and reflecting. The subjects In this study, there was group B Taman Kanak-Kanak Negeri Pembina Polewali Village, Gantarang District, Bulukumba Regency. Data collection techniques were observation and documentation. The results of the study indicated that by using the media block numbers could improve the ability to recognize the symbol of child numbers in group B in Taman Kanak-Kanak Negeri Pembina Polewali Village Gantarang District Bulukumba Regency. In Cycle I the percentage of children's results was 60% and increased to 87% in cycle II.Keywords: Ability to Recognize Symbol Number, Number Beams.